The Khaki Boys at Camp Sterling; Or, Training for the Big Fight in France - Chase, Josephine, -1931 (Salt Lake City, UT : Project Gutenberg, 2014)
"The Khaki Boys at Camp Sterling; Or, Training for the Big Fight in France" by Capt. Gordon Bates is a military-themed novel written in the early 20th century, likely during the World War I era. The book follows a group of young American soldiers, particularly focusing on characters such as Jimmy Blaise and Roger Barlow, as they enlist in the Army and begin their training at Camp Sterling, preparing for service in France. The story captures their experiences, challenges, and camaraderie as they embark on this journey together. The opening of the novel introduces the patriotic fervor of the time, with young boys actively recruiting for the war effort. We meet Jimmy, a lively character, who encourages Roger to enlist alongside him. Their friendship quickly develops as they make their way to the recruiting station and subsequently prepare for training at Camp Sterling. The narrative sets a tone of youthful enthusiasm and a sense of purpose, delving into themes of bravery and the bonds of friendship formed in the face of adversity. The characters are depicted with distinct personalities and backgrounds, hinting at their individual journeys ahead as they adapt to military life. (This is an automatically generated summary.)
Release date is 2014-06-18
E-text prepared by Juliet Sutherland, Joke Van Dorst, and the Online Distributed Proofreading Team
Keywords: World War, 1914-1918 -- Juvenile fiction